Sağlıklı Bir Kişide Mental Yorgunluk Dengeyi Bozar Mı? - Demircan, Emine Nur; Ruşen, Ece; Köse, Nezire (Hacettepe University Faculty of Health Sciences Journal)
Objectives: This study was conducted to determine whether mental fatigue was the cause of the balance disorder experienced by a healthy person who did not experience any balance disorder in daily life during work life. Materials and Methods: healthy female client who applied to our department due to balance disorder did not have any balance disorder in her daily life, but she had balance problems during very busy working days, and there were no negative results in all her medical examinations. After the history, the lower extremity muscle strength and endurance, proprioception, cognitive status and balance were evaluated. Mental Fatigue (MF) was created in the person with Verbal Memory Processes Test and Animal Fluency Test, all evaluations were repeated. The same procedures were repeated a day later, with balance tests performed along with an additional task. Thus, balance tests were made a little more difficult and the effect of the dual task on balance activity and cognitive status was examined. Results: At the end of the study, the balance of the person was adversely affected with MF, the balance was further deteriorated in the balance activity performed with an additional task, cognitive function decreased after this activity. It was determined that the balance of standing on the weaker extremity was even more impaired. Conclusion: At the end of the study; Although there is no medical problem that may cause balance problems in people, it was concluded that MF and dual-task activities may have a negative effect on balance, and lower extremity muscle strength, endurance and proprioception may increase the negative effects on dynamic balance in addition to MF.